Sociodemographic risk factors and correlates of dementia in older Malaysians - Tengku Abdul Hamid, Tengku Aizan; Krishnaswamy, Saroja; Abdullah, Siti Suhailah; Momtaz, Yadollah Abolfathi (S. Karger, 2010)
Objective: The rapid expansion of the aged population in Malaysia is expected to greatly increase the number of persons with dementia in the country. However, data on dementia prevalence at the national level is lacking, and little is known about the sociodemographic risk factors and correlates of dementia. This paper describes a nationwide study of dementia prevalence and its sociodemographic risk factors and health correlates among older Malaysians. Methods: In the nationwide study, the Mental Health and Quality of Life of Older Malaysians, AGECAT-GMS was used to diagnose dementia in a nationally representative sample of 2,980 persons aged 60 and above. Results: The prevalence rate of dementia was 14.3%. Higher dementia prevalences were found in oldest age (26.3%), women (19.7%), no formal education (24.1%), Bumiputeras (32.2%), unmarried (19.4%), unemployed (31.3%) and very poor on self-rated health (33.3%). Multivariate logistic regression analyses showed that older age, female gender, no formal education, ethnicity and very poor self-rated health were independent risk factors and correlates of dementia. Conclusions: Relatively higher prevalence rates of dementia in older Malaysians were accounted for by greater proportions without education, Malay and Bumiputera ethnicity, and other unknown factors which should be further investigated.